Contribution of Virus-Receptor Interaction to Distinct Viral Proliferation of Neuropathogenic and Nonneuropathogenic Murine Leukemia Viruses in Rat Glial Cells - Takase-Yoden, Sayaka (American Society for Microbiology, 1999)
The efficiency of receptor-mediated entry of pseudotyped virus carrying the surface protein (SU) of clone A8, a neuropathogenic variant of Friend murine leukemia virus (FrMLV), to rat glial cell line F10 was 1 order of magnitude greater than that of pseudotyped virus carrying SU of nonneuropathogenic FrMLV clone 57. Introduction of the gene coding for ecotropic MLV receptor on F10 cells (F10-ecoR) into SIRC cells, which are naturally resistant to FrMLV infection, also revealed the difference in receptor recognition between the A8 and the 57 viruses. Our results show that the difference in receptor utilization between A8-SU and 57-SU only partially explains the 3-order-of-magnitude difference in proliferation between A8 and 57 viruses in F10 cells.